Portrait of Ecology-Based Da’wah in Ambon City - Hakis, Hakis; Kamaluddin, Kamaluddin; Nur, Syamsuddin; Usman, ST. Syahruni (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2024)
The purpose of this research is to find a portrait of ecology-based da'wah in Ambon city. This research uses descriptive qualitative research methods supported by quantitative data with a phenomenological approach in the form of field research. The results showed that the portrait of ecology-based da'wah in Ambon city found five dominant objects of study that can contribute to ecological improvement in Ambon city, which are summarized in three da'wah methods, namely; Da'wah bi al-lisan as a pattern of ecological da'wah campaigns in the form of da'wah through pulpits, ecology-based counseling and socialization. Da'wah bi al-Qalam as a pattern of publication of ecological da'wah in the form of information messages through media based on ecological da'wah, and Da'wah bi Hal (actions) as a pattern of initiation of ecological da'wah in the form of environmental care actions and environmental rescue organizations. Of the three findings of the da'wah method, the most dominant in contributing to ecological improvement in Ambon is the Environmental Rescue Organization with 56% stating that it exists and 44% stating that it does not exist, while the other is Media Messages About the Environment with the acquisition of 52% stating that it exists and 48% stating that it does not exist. And the least contributing to ecological improvement is da'wah through the pulpit with the acquisition of 32% existing and 68% who stated that it did not exist. Therefore, it is suggested to the authorities to pay attention to ecology-based da'wah in order to save the environment in Ambon city.